Pendanaan Pendidikan Anak Usia Dini - Josepha Maria Tedjawati (Jurnal Pendidikan dan Kebudayaan, 2013)
This study aimed to describe the funding for early childhood education and the amount of funding from each source. This study used a qualitative approach through case studies in eight districts/cities. Research methods used in the research is descriptive quantitative. The study results show that: First, early childhood education funding generally comes from the central government and the regions. However, it is perceived still not sufficient for the operational costs of early childhood education. During this time, local governments still prioritize for compulsory education program. Funds coming from the public and agency/business/industry is still limited and depends on the economic ability and willingness of agencies/business/industry. Funds coming from the providers are not sufficient, it is highly dependent on parents income. Second, assistance from the government and donations from community institutions compases of money, educator incentives, and educational toys, books, medicine, and health check for students.